Lysine-Specific Demethylase 2 Suppresses Lipid Influx and Metabolism in Hepatic Cells - Nagaoka, Katsuya (Mol Cell Biol, 2015)
Cells link environmental fluctuations, such as nutrition, to metabolic remodeling. Epigenetic factors are thought to be involved in such cellular processes, but the molecular basis remains unclear. Here we report that the lysine-specific demethylase 2 (LSD2) suppresses the flux and metabolism of lipids to maintain the energy balance in hepatic cells. Using transcriptome and chromatin immunoprecipitation-sequencing analyses, we revealed that LSD2 represses the genes involved in lipid influx and metabolism through demethylation of histone H3K4. Selective recruitment of LSD2 at lipid metabolism gene loci was mediated in part by a stress-responsive transcription factor, c-Jun. Intriguingly, LSD2 depletion increased the intracellular levels of many lipid metabolites, which was accompanied by an increased susceptibility to toxic cell damage in response to fatty acid exposure. Our data demonstrate that LSD2 maintains metabolic plasticity under fluctuating environment in hepatocytes by mediating the cross talk between the epigenome and metabolism.